2017
DOI: 10.1007/s11019-017-9785-y
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions and moral understanding of the wish to hasten death: a philosophical review of qualitative studies

Abstract: It is not uncommon for patients with advanced disease to express a wish to hasten death (WTHD). Qualitative studies of the WTHD have found that such a wish may have different meanings, none of which can be understood outside of the patient's personal and sociocultural background, or which necessarily imply taking concrete steps to ending one's life. The starting point for the present study was a previous systematic review of qualitative studies of the WTHD in advanced patients. Here we analyse in greater detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…Nurses can also prepare themselves by reflecting on the substantive issues that are coming to the fore in a request of this nature. In their philosophic analysis of qualitative studies of the wish to hasten death, Rodriguez-Prat and van Leeuwen50 identified 4 moral themes inherent in these requests: dignity, autonomy, and authenticity; social interactions; the value of life; and the medicalization of care. As nurses reflect on these themes and how they influence a request to hasten death, they will be better prepared to engage authentically with patients across the spectrum of these evolving contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses can also prepare themselves by reflecting on the substantive issues that are coming to the fore in a request of this nature. In their philosophic analysis of qualitative studies of the wish to hasten death, Rodriguez-Prat and van Leeuwen50 identified 4 moral themes inherent in these requests: dignity, autonomy, and authenticity; social interactions; the value of life; and the medicalization of care. As nurses reflect on these themes and how they influence a request to hasten death, they will be better prepared to engage authentically with patients across the spectrum of these evolving contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Third, MAiD is new to Canada. Even though healthcare providers have always received requests to hasten death, only now do they have the legal authority to do so [22,23]. Further, the experience of the death itself is vastly different from a normal death [8].…”
Section: Delegation: Supports As a Reflection Of Sociocultural Contextmentioning
confidence: 99%
“…It covers situations where practitioners provide lethal drugs to people, or administer it to them, to hasten their deaths. The deliberate causing of one's own death and the intentional allowing or causing of the death of other people are, however, highly emotional and morally sensitive issues (Cholbi, 2017;Rodríguez-Prat & van Leeuwen, 2018). The public policy in Western countries is therefore to protect the sanctity of life and this together with the policy to protect vulnerable people from potential abuse, is an obstacle for those who advocate for euthanasia (Pretty v United Kingdom, 2002;Rodriguez v. British Columbia [Attorney General], 1993).…”
Section: Suicidementioning
confidence: 99%
“…These include wanting to control how they die and to ensure it is dignified (Rehmann-Sutter, Gudat, & Ohnsorge, 2015;Rodríguez-Prat & van Leeuwen, 2018). Others' ideation could be part of their adjustment to the dying process (Johnson, Cramer, Gardner, & Nobles, 2015) and psychologists should not confuse these clients' prospective grief and fear of dying, the unknown, and pain with anxiety and depression (Farberman, 1997).…”
Section: Clients Who Desire To Diementioning
confidence: 99%